Sarcopenia and post-operative complications in patients undergoing gastrectomy for gastric cancer: Integrative review (Revista Contexto & Saúde, 2023)
The objective is to investigate the influence of sarcopenia on postoperative complications in patients undergoing gastrectomy for gastric cancer. PubMed, Cochrane, Science Direct and Scielo databases were used, with the descriptors Sarcopenia and Stomach Neoplasms. The integrative review was structured with fifteen articles, between 2015 and 2019. Data analysis was performed descriptively. Twelve studies identified sarcopenia as a risk factor for postoperative complications in patients undergoing gastrectomy for gastric cancer. The reduction in skeletal muscle mass is associated with decreased nutrient intake or bioavailability and metabolic changes, such as increased production of pro-inflammatory molecules resulting in a weakened immune system and poor post-surgical healing. It was concluded that the presence of sarcopenia in patients undergoing gastrectomy for gastric cancer is related to a higher occurrence of complications in the postoperative period.
Keywords: Postoperative complications; Gastrectomy; Skeletal muscle; Gastric neoplasms; Sarcopenia